Early Detection of Determination Factors Stock Price Increase - Rifqi Aliza Syukhron; Aprih Santoso; Ardiani Ika Sulistyawati (Universitas Muhammadiyah Sorong, 2022)
The purpose of this study was to examine the effect of CR, ROE, DER, ROA on stock prices of pharmaceutical sub-sector companies listed on IDX) 2013-2019. The population of this research is all pharmaceutical sub-sector companies listed on IDX during 2013-2019, which amount to 8 companies. The technique of determining the sample is by purposive sampling. The test instruments used in this research are: normality test, heteroscedasticity test, multicollinearity test, coefficient of determination, model test (F test) and hypothesis test (t test). The data analysis method used multiple linear regression. The results show that there is no influence between CR, DER and ROE on stock prices in pharmaceutical sub-sector companies listed on IDX in 2013-2019. . There is a positive and significant influence between ROA on the company's stock price, in the pharmaceutical sub-sector companies listed on IDX in 2013-2019).